The Charlie Taxiway Design And South Apron At Adi Soemarmo Boyolali Internasional Airport - Syairi Anwar; Muhammad Caesar Akbar; Raihan Abi Yunanda (Sean Institute, 2024)
On the job training activities at Adi Soemarmo Boyolali International Airport there are three things that are of concern, namely the problem with the color of the apron lights on the south side using red lights, where according to the regulations the color of the apron lights on the south side must be blue. And the electrical system for the Taxiway Edge lights are old components that were installed in 1980, and also the electrical lines for the Taxiway Edge lights still use 1 circuit. The problem with the South Apron lights is that they do not comply with the standards of the Ministry of Transportation regulations number:. KP 39 of 2015 Concerning Technical and Operational Standards for Civil Aviation Safety Regulations - Part 139 (Manual of CASR Standards - Part 139) Volume I Airports (Aerodromes), Then the problem with the Taxiway Edge lights is that the continuity of spare parts does not meet and it is difficult to find components. The tool components are due to the old production year, and also still use 1 circuit on the Taxiway Edge lamp electrical line. Based on this background, the author intends to present a report with the title